Enzymatic single-step preparation and antioxidant activity of hetero-chitooligosaccharides using non-pretreated housefly larvae powder. (15th September 2017) - Zhang, Yang; Zhou, Xiuling; Ji, Lusha; Du, Xiuju; Sang, Qing; Chen, Fang
Highlights: A novel chitinolytic enzyme-producing bacterium Chitiniphilus sp. LZ32 was isolated. Housefly larvae powder can be used for synthesis of chitooligosaccharides. Simple process of chitooligosaccharide production using HLP was realized. COS-72 exhibited the strongest hydroxyl-scavenging ability and reducing power. Abstract: A novel chitinolytic enzyme-producing bacterium Chitiniphilus sp. LZ32 was isolated. Non-pretreated Housefly larvae powder (HLP) was used as an adsorbent to purify chitinolytic enzymes. The optimal conditions for hydrolysis of HLP by purifying enzymes chitinolytic enzymes were investigated. HPLC and MALDI-TOF analyses indicated that HLP enzymatic hydrolyzates mainly contain N-acetylglucosamine (GlcNAc) and hetero-chitooligosaccharides (COS) composed of GlcN and GlcNAc. The hetero-chitooligosaccharides (COS) had a degree of polymerization (DP) in the 2–6 range. The maximum production of COS was 158.3 μg/mL after 72 h of incubation. Maximum pentamer (51.2 μg/mL) and hexamer concentrations (36.1 μg/mL) were achieved at hydrolysis times of 72 and 84 h, respectively. Antioxidant activities of purified COS products (PCOS) from different hydrolysis times were investigated in vitro. PCOS produced by hydrolysis times of 72 h (PCOS-72) exhibited the strongest hydroxyl-scavenging ability and reducing power. These results indicate the potential of Chitiniphilus sp. LZ32 for COS production using HLP.